Outcome of Continuous Positive Airway Pressure Adherence Based on Nasal Endoscopy and the Measurement of Nasal Patency-A Prospective Study - Knížek, Zdeněk; Kotulek, Miloš; Brothánková, Pavlína; Pecháčková, Eva; Klail, Pavel; Kostlivý, Tomáš; Vodička, Jan (Life (Basel, Switzerland), 2023)
The gold standard for treating obstructive sleep apnea in adults is continuous positive airway pressure (CPAP). However, it can be difficult to convince patients to adhere to this therapy. The aim of this study was to determine the relationship between nasal endoscopy findings/nose patency and CPAP adherence. Material and methods: A cohort of 450 consecutive patients suspected of having OSA were prospectively enrolled. For further analyses, 47 OSA patients undergoing CPAP treatment were selected (13 females and 34 males, average age, 65.3 years, BMI 34.1, apnea-hypopnea index. AHI 51.0). The patients were divided into two groups: patients with good CPAP adherence (n = 35) and patients who did not adhere to CPAP therapy (n = 12). The influence of nasal endoscopy and flow measurement on CPAP adherence was explored. Results: We found a statistical independence between adherence to CPAP and AHI (p = 0.124), T90 (p = 0.502), endoscopic findings (p = 0.588) and nasal patency measured by a flowmeter (p = 0.498). Conclusions: In our studied sample, endoscopic findings and nasal patency measured by a flowmeter were not predictors of CPAP non-adherence in the first year of the treatment. Our data show that while an endoscopic finding in the nasal cavity could indicate that a patient has a severe obstruction, compliance with CPAP therapy is not reduced in these patients and neither is it reduced with a decrease in nasal flow, according to our observation.
Keywords: OSA; nasal obstruction; CPAP; flow measurement